Buckling analysis of a delaminated panel by using a kinematic global-local coupling approach. Issue 4 (11th November 2014) - Sellitto, A.; Borrelli, R.; Caputo, F.; Riccio, A.; Scaramuzzino, F.
Abstract : Purpose: – The purpose of this paper is to investigate on the behaviour of a delaminated stiffened panel; the delamination growth is simulated via fracture elements implemented in B2000++® code based on the Modified Virtual Crack Closure Technique (MVCCT), matrix cracking and fibre failure have been also taken into account. Design/methodology/approach: – In order to correctly apply the MVCCT on the delamination front a very fine three-dimensional (3D) mesh is required very close to the delaminated area, while a 2D-shell model has been employed for the areas of minor interest. In order to couple the shell domain to the solid one, shell-to-solid coupling elements based on kinematic constraints have been used. Findings: – Results obtained with the global/local approach are in good correlation with those obtained with experimental results. Originality/value: – The global/local approach based on kinematic coupling elements in conjunction with fracture elements allows to investigate and predict the behaviour of a stiffened delaminated composite panel in an efficient and effective way.